Improving preprocedure antithrombotic management: Implementation and sustainment of a best practice alert and pharmacist referral process. Issue 5 (16th July 2021) - Han, Henry; Chung, Grace; Sippola, Emily; Chen, Wilson; Morgan, Spencer; Renner, Elizabeth; Ruff, Allison; Sales, Anne; Kurlander, Jacob; Barnes, Geoffrey D.
Abstract: Background: Electronic medical record–based interventions such as best practice alerts, or reminders, have been proposed to improve evidence‐based medication prescribing. Formal implementation evaluation including long‐term sustainment are not commonly reported. Preprocedural medication management is often a complex issue for patients taking antithrombotic medications. Methods: We implemented a best practice alert (BPA) that recommended referral to an anticoagulation clinic before outpatient elective gastrointestinal (GI) endoscopies. Eligible patients were taking an oral anticoagulant (warfarin or direct oral anticoagulant [DOAC]) and/or antiplatelet medications. Patients referred to the anticoagulation clinic were compared to those managed by the ordering provider. Outcomes assessed included guideline‐adherent drug management before endoscopy, documentation of a medication management plan, guideline‐adherent rates of bridging for high‐risk patients taking warfarin, and evaluation for sustained use of BPA. Results: Eighty percent of patients (553/691) were referred to the anticoagulation clinic during the initial 13‐month study period. Most referrals came from gastroenterologists (397/553; 71.8%) followed by primary care providers (127/554; 22.9%). Patients referred had improved rates of guideline‐adherent medication management compared to those who were not referred (97.4% vs 91.0%; P  = .001). Documentation of medication plan was significantly higher in the referred group (99.1% vs 59.4%; P  ≤ .001). There were no differences in rates of appropriate bridging for patients taking warfarin. Implementation of the BPA also resulted in sustained, consistent use over an additional 18 months following the initial study period. Conclusion: Implementation of a BPA before elective outpatient GI endoscopies was associated with improved rates of guideline‐adherent medication management and documented management plan, while streamlining preprocedural medication management.